The application of simulation methods as a tool for the construction of expert long-term forecasts - Szkutnik, Tomasz (Zastosowanie metod symulacyjnych jako narzędzia do konstrukcji eksperckich prognoz długookresowych, 2011)
The application of simulation methods allows for the consideration of the influence of key events in the case of determining long-term forecasts. The influence of events upon the base values of different nature, strength of the influence, frequency of their occurrence or the time of occurrence may be difficult in the case of constructing a classic model. The simulation approach allows not only for the determination of the total influence but also for the consideration of particular cases and the performance of a wide range of diagnostic tests that verify the strength of influence of the adopted hypotheses. The accepted methodology of determining the forecasts may be applied not only in the foresight research. In reality it was originally created for such a research and here it may find the broadest application.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 222-231
Keywords: badanie diagnostyczne; prognozowanie; diagnostic test; forecasting